Model Strategi Pengembangan Sumber Daya Manusia Nelayan Pengolah Hasil Tangkapan Di Pesisir Pantai Selatan Cilacap Jawa Tengah dalam Menghadapi Persaingan Pasar Global - Hari Sucahyowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2019)
The purpose of this study was to formulate a strategy model for human resource fisherman development in the South Coast of Cilacap in the face of the National Market using the soft system methodology (SSM) approach. This study resulted in a conceptual modeling of the strategy of developing the human resources of stakeholders (stakeholders) with increasing productivity in realizing the welfare and sustainability of Catcher Processing Fishermen in the South Coast of Cilacap, Central Java. The strategy for developing Fishermen Processing Fishermen in the South Coast of Cilacap, Central Java is a strategic action to generate competency and quality of fishermen with high competitiveness, especially in facing local competition and national competition through various HR capacity development programs. HR investment is an intellectual investment that has an important meaning for regional development and enhances the welfare of the people of South Coast Coastal Fishermen, Cilacap, Central Java.